Cardiovascular Events According to Inhaler Therapy and Comorbidities in Chronic Obstructive Pulmonary Disease - Kim EK; Lee E; Park JE; Lee JS; Choi HS; Park B; Sheen SS; Park KJ; Rhee CK; Lee SY; Yoo KH; Park JH (International Journal of COPD, 2024)
Eun Kyung Kim,1,* Eunyoung Lee,2,* Ji Eun Park,3,* Jae Seung Lee,4 Hye Sook Choi,5 Bumhee Park,6,7 Seung Soo Sheen,3 Kwang Joo Park,3 Chin Kook Rhee,8 Sang Yeub Lee,9 Kwang Ha Yoo,10 Joo Hun Park3 1Department of Pulmonology, Allergy and Critical Care Medicine, CHA Bundang Medical Center, CHA University, Seongnam, Republic of Korea; 2Department of Neurology, McGovern Medical School at UTHealth, Houston, TX, USA; 3Department of Pulmonary and Critical Care Medicine, Ajou University School of Medicine, Suwon, Republic of Korea; 4Department of Pulmonary and Critical Care Medicine, Asan Medical Center, University of Ulsan College of Medicine, Seoul, Republic of Korea; 5Department of Internal Medicine, Kyung Hee University Medical Center, Seoul, Republic of Korea; 6Office of Biostatistics, Medical Research Collaborating Center, Ajou Research Institute for Innovative Medicine, Ajou University Medical Center, Suwon, Republic of Korea; 7Department of Biomedical Informatics, Ajou University School of Medicine, Suwon, Republic of Korea; 8Department of Internal Medicine, Seoul St. Mary’s Hospital, Catholic University of Korea, Seoul, Republic of Korea; 9Department of Internal Medicine, Korea University Anam Hospital, Seoul, Republic of Korea; 10Department of Internal Medicine, Konkuk University School of Medicine, Seoul, Republic of Korea*These authors contributed equally to this workCorrespondence: Joo Hun Park, Department of Pulmonary and Critical Care Medicine, Ajou University School of Medicine, Worldcup Road 164, Suwon, Gyeonggi-do, 16499, Republic of Korea, Tel +82-31-219-5116, Fax +82-31-219-5124, Email jhpamc@naver.com; jhpamc@hanmail.netBackground: COPD coexists with many concurrent comorbidities. Cardiovascular complications are deemed to be major causes of death in COPD. Although inhaler therapy is the main therapeutic intervention in COPD, cardiovascular events accompanying inhaler therapy require further investigation. Therefore, this study aimed to investigate new development of cardiovascular events according to each inhaler therapy and comorbidities.Methods: This study analyzed COPD patients (age ≥ 40 years, N = 199,772) from the Health Insurance Review and Assessment Service (HIRA) database in Korea. The development of cardiovascular events, from the index date to December 31, 2020, was investigated. The cohort was eventually divided into three arms: the LAMA/LABA group (N = 28,322), the ICS/LABA group (N = 11,812), and the triple group (LAMA/ICS/LABA therapy, N = 6174).Results: Multivariable Cox analyses demonstrated that, compared to ICS/LABA therapy, triple therapy was independently associated with the development of ischemic heart disease (HR: 1.22, 95% CI: 1.04– 1.43), heart failure (HR: 1.45, 95% CI: 1.14– 1.84), arrhythmia (HR: 1.72, 95% CI: 1.41– 2.09), and atrial fibrillation/flutter (HR: 2.31, 95% CI: 1.64– 3.25), whereas the LAMA/LABA therapy did not show a significant association. Furthermore, emergency room visit during covariate assessment window was independently associated with the development of ischemic heart disease, heart failure, arrhythmia, and atrial fibrillation/flutter (p < 0.05).Conclusion: Our data suggest that cardiovascular risk should be considered in COPD patients receiving triple therapy, despite the confounding bias resulting from disparities in each group.Keywords: COPD, inhaler therapy, cardiovascular event, comorbidities